Long recall loss in estimates of rural labor supply: Evidence from phone surveys in Malawi - Ambler, Kate; Herskowitz, Sylvan; Maredia, Mywish K. (International Food Policy Research Institute, 2021)
The measurement of labor supply in developing countries has always faced a tradeoff between accuracy and detail. Accuracy is thought to be maximized by using short recall periods. However, these short snapshots fail to capture seasonal labor happening at different times of year. By contrast, long recall windows of up to a year or longer, may, in theory, cover the full range of annual productive activities, but also suffer from greater distortions due to the challenges of recalling activities in the distant past.